TREATMENT PROCESSES BASED ON THE MOLECULAR WEIGHT DISTRIBUTION OF TEXTILE DYEING WASTEWATER - Yaman, Fatma Busra; Cakmakci, Mehmet; Karadag, Dogan; Ozkaya, Bestamin; Bali, Vesile; Dora, Billur (TECHNICAL UNIV WROCLAW, 2018)
Rinsing wastewater from dyeing and bleaching processes in a cotton dyeing facility has been separately characterized to evaluate the suitable treatment processes and reuse options. Alternative treatment processes were proposed based on molecular weight distribution (MWD), ultraviolet absorbance of 254 nm (UV254) and specific ultraviolet absorbance (SUVA). Rinsing wastewater samples were sequentially filtrated to determine the MWD of 5-day biochemical oxygen demand (BOD5), chemical oxygen demand (COD), dissolved organic carbon (DOC), total Keldahl nitrogen (TKN) and ammonium (NH4+). Bleaching rinsing wastewater had higher organic and nitrogen contents than dyeing rinsing wastewater and concentrations of pollutants decreased after each membrane filtration step. During the sequential filtration, BOD5/COD ratio in bleaching rinsing wastewater slightly decreased while it significantly increased in dyeing rinsing wastewater. SUVA values indicated that organic matters in the rinsing wastewaters have hydrophilic characteristics in all conditions. The evaluation of all experimental data indicates that combination of anaerobic treatment and NF membrane filtration could provide high quality water for reuse within the facility and discharge into receiving environments.
Keywords: BIOLOGICAL TREATMENT; REVERSE-OSMOSIS; MEMBRANE; NANOFILTRATION; REUSE; CONCENTRATE; FRACTIONS; LEACHATE; Engineering